The Impact of Lifetime Work and Non-work Physical Activity on Physical Fitness Among White – and Blue – Collar Retirees: A Cross-Sectional Study - Trzmiel, Tomasz; Pieczyńska, Anna; Zasadzka, Ewa; Pawlaczyk, Mariola (Frontiers in Medicine, 2021)
Objective: The literature offers significant amount of data on the effects of occupational activity on health, with a distinct link between retirement and health among the most frequently tackled topics. Studies on the relationship between past occupational activity and physical fitness among older retirees remain scarce. The aim of the study was to assess the effects of physical activity on physical fitness in white- and blue-collar retirees. Methods: A total of 200 participants (aged ≥60) were included in the study. Lifetime physical activity was assessed using the Lifetime Physical Activity Questionnaire. Mean MET/week/year values of total Physical Activity and for each domain separately (occupational, sports, household) were calculated. Participants were stratified to blue- or white- collar group. Physical performance, hand-grip strength (HGS) and pulmonary function were assessed. Results: Mean total MET/week/year values for the blue- and the white-collar workers were 140.48±55.13 and 100.75±35.98, respectively. No statistically significant differences in physical performance scores were found between the white- and blue-collar groups. Adjustment for age, sex weight and height revealed a statistically significant association between work-related PA FEV*1 in the blue-collar group. White – collar workers presented higher odds ratio for membership in highest quartile in regard to short physical performance battery test score. Conclusion: Only minimal association of type of occupation on physical fitness were found despite statistically significant differences between mean intensity and duration of sports- and work-related lifetime physical activity. These findings may indicate that the type of past work is not an independent factor influencing the state of a person in old age. Large-scale investigations with physically fit and unfit participants, are necessary.